Naskah undang-undang Melaka: Suatu tinjauan - Liaw, Yock Fang (Universiti Kebangsaan Malaysia, 2007)
This article results from the writer’s 35 years of research on Undang-Undang Melaka (The Laws of Malacca). It points out that it is not easy to define this body of manuscripts, let alone study them. Firstly, an inventory of the manuscripts had to be made. This undertaking was made difficult by the fact that many of them go under a variety of titles. The term Undang-Undang Melaka itself is known to have fourteen different names. Secondly, one single manuscript may have multiple distinguishable texts sorted under it. Thirdly, the integrity of the existing catalogue of manuscripts is very much in question. Fourthly, there exist manuscripts that are not mentioned in the catalogue. Lastly, new relevant manuscripts may continue to appear from private collections now and then